Definition of the right to nature usage: theoretical aspects - Shakhray, Irina S. (Journal of the Belarusian State University. Law, 2021)
The article examines conceptual approaches to the definition of the «nature management right». Based on the analysis of scientific sources, legislation of the Republic of Belarus and other post-Soviet states, a conclusion was made about the validity of understanding the right to nature usage in a narrow sense, covering the use of natural resources (the entire range of their useful properties), but not all types of environmental impacts. This approach allows us to take into account peculiarities of natural resource relations, differentiate them with environmental relations and bring together the legal status of users of various natural resources. The features of natural resources are considered, a conclusion is made about the need to clarify this concept and consolidate their general list in the law on environmental protection. Proposals are being formulated to improve a number of provisions of this law and natural resources legislation.